Role of Nicotine Dependence in the Association between the Dopamine Receptor Gene DRD3 and Major Depressive Disorder - Korhonen, Tellervo; Loukola, Anu; Wedenoja, Juho; Nyman, Emma; Latvala, Antti; Broms, Ulla; Häppölä, Anja; Paunio, Tiina; Schrage, Andrew J.; Vink, Jaqueline M.; Mbarek, Hamdi; Boomsma, Dorret I.; et al. (PLOS ONE, 2014)
Background The aims of this study were to analyze associations of dopamine receptor genes (DRD1-5) with Major Depressive Disorder (MDD) and nicotine dependence (ND), and to investigate whether ND moderates genetic influences on MDD. Methods The sample was ascertained from the Finnish Twin Cohort. Twin pairs concordant for smoking history were recruited along with their family members, as part of the multisite Nicotine Addiction Genetics consortium. Genetic association analyses were based on 1428 adults. Total of 70 tagging single nucleotide polymorphisms within the dopamine receptor genes were genotyped and analyzed for association with MDD, ND, and MD-ND co-morbidity. Individual level logistic regression analyses were based on 1296 adults with data on ND and MDD diagnoses, as well as on dopamine receptor genotypes adjusted for sex, age, and alcohol use. Four independent samples, such as population-based and case-control samples, were used for replication. Results Rs2399496, located 1.5 kb downstream of DRD3, showed suggestive association for MDD (p = 0.00076) and significant association for MDD-ND co-morbidity (p = 0.000079). Suggestive gene-(rs2399496) by-ND-interaction justified analyses by genetic risk variant and ND status. Individuals with ND and two minor alleles (AA) of rs2399496 had almost six-fold risk for MDD (OR 5.74, 95%CI 3.12–10.5, p = 9.010e-09) compared to individuals without ND and with two major alleles (TT). Conclusions Significant association between a variant downstream of DRD3 and a co-morbid MDD-ND phenotype was detected. Our results further suggest that nicotine dependence may potentiate the influence of the DRD3 genetic variant on MDD.